Analysis of Differentially Expressed Genes of Chrysoperla sinica Related to Flight Capacity by Transcriptome. Issue 1 (23rd February 2021) - Liu, Zhong-Fang; Liang, Yao-yao; Sun, Xiao-ting; Yang, Jing; Zhang, Peng-Jiu; Gao, Yue; Fan, Jian-Bin; Fan, Ren-Jun
Abstract: The lacewing Chrysoperla sinica (Tjeder) is a common natural enemy of many insect pests in China and is frequently employed for biological control programs. Adults make migratory flights after emergence, which reduces their effectiveness as biological control agents. Previously, we proved that 2-d-old unmated females exhibited significantly stronger flight ability than 3-d-old ones. Meanwhile, 3-d-old unmated adults flew significantly longer distances than mated ones. In this study, Illumina RNA sequencing was performed to characterize differentially expressed genes (DEGs) between virgin and mated adults of different ages in a single female strain of C. sinica . In total, 713, 563, 726 clean reads were obtained and de novo assembled into 109, 165 unigenes with an average length of 847 bp (N50 of 1, 754 bp), among which 4, 382 (4.01%) unigenes matched known proteins. Based on these annotations, many putative transcripts were related to C. sinica 's flight capacity and muscle structure, energy supply, growth, development, environmental adaptability, and metabolism of nutritional components and bioactive components. In addition, the differential expression of transcripts between different ages and mating status were analyzed, and DEGs participating in flight capacity and muscles were detected, including glutathione hydrolase, NAD-specific glutamate dehydrogenase, aminopeptidase, and acidic amino acid decarboxylase. The DEGs with functions associated with flight capacity and muscles exhibited higher transcript levels for younger (2 d--old) virgins. This comprehensive C. sinica transcriptomic data provide a foundation for a better understanding of the molecular mechanisms underlying the flight capacity to meet the physiological demands of flight muscles in C. sinica .